Delayed Presentation of Tetralogy of Fallot with Isolated Cyanosis - Zachary Zemore; Avni Sharma; Kerri Carter; Aline Baghdassarian (Case Reports in Pediatrics)
A pediatric patient with hypoxia or cyanosis can frighten even the most seasoned emergency providers. Patients with these symptoms require immediate evaluation and intervention to stabilize their condition. While the differential can be broad, specific attention must be paid to cardiopulmonary etiologies. Tetralogy of Fallot is the most common cyanotic congenital heart abnormality, and routine screening surprisingly misses a significant amount of these cases. This case serves as an example of a missed diagnosis by screening efforts and reaffirms the resuscitation algorithm of a hypoxic pediatric patient that all emergency providers should be familiar with.